2011
DOI: 10.1016/j.bpj.2011.01.022
|View full text |Cite
|
Sign up to set email alerts
|

The β1a Subunit of the Skeletal DHPR Binds to Skeletal RyR1 and Activates the Channel via Its 35-Residue C-Terminal Tail

Abstract: Although it has been suggested that the C-terminal tail of the β(1a) subunit of the skeletal dihyropyridine receptor (DHPR) may contribute to voltage-activated Ca(2+) release in skeletal muscle by interacting with the skeletal ryanodine receptor (RyR1), a direct functional interaction between the two proteins has not been demonstrated previously. Such an interaction is reported here. A peptide with the sequence of the C-terminal 35 residues of β(1a) bound to RyR1 in affinity chromatography. The full-length β(1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…Following closely on the heels of the generation of the β 1 null mouse, a series of studies employing expression of β 1a deletion mutants and β 1a -β 2a chimeras in null mouse myotubes demonstrated that the distal carboxyl terminus of β 1a was a critical component for the maintenance of skeletal-type EC coupling (Beurg et al, 1999;Sheridan et al, 2003aSheridan et al, ,b, 2004. In broad agreement with these data, a carboxyterminal fragment of β 1a corresponding to its final 35 residues (V490-M524) was shown to stick to RyR1 in vitro and to promote channel opening in planar lipid bilayers (Rebbeck et al, 2011). A similar, but shorter peptide (V490-M508) activated RyR1 in a later study (Hernández-Ochoa et al, 2014).…”
Section: Introductionsupporting
confidence: 53%
“…Following closely on the heels of the generation of the β 1 null mouse, a series of studies employing expression of β 1a deletion mutants and β 1a -β 2a chimeras in null mouse myotubes demonstrated that the distal carboxyl terminus of β 1a was a critical component for the maintenance of skeletal-type EC coupling (Beurg et al, 1999;Sheridan et al, 2003aSheridan et al, ,b, 2004. In broad agreement with these data, a carboxyterminal fragment of β 1a corresponding to its final 35 residues (V490-M524) was shown to stick to RyR1 in vitro and to promote channel opening in planar lipid bilayers (Rebbeck et al, 2011). A similar, but shorter peptide (V490-M508) activated RyR1 in a later study (Hernández-Ochoa et al, 2014).…”
Section: Introductionsupporting
confidence: 53%
“…In cardiac muscle, upon excitation, cytosolic Ca 2+ is rapidly increased by coordinated DHPR and RyR channel opening that couples Ca 2+ influx from the extracellular space with release from SR stores, in a process of Ca 2+ induced Ca 2+ release (CICR). In skeletal muscle, a voltage-dependent conformational change in DHPR causes opening of RyRs through Ca 2+ -independent mechanical coupling of DHPRs with the cytoplasmic domain of the RyRs at MCSs, in a process termed voltage-initiated Ca 2+ release (VICR) [3,51].…”
Section: Er-plasma Membrane Contact Sitesmentioning
confidence: 99%
“…The disruption of this region not only prevents ␤ 1a -RyR1 interactions in vitro but also weakens electrically evoked Ca 2ϩ release signals in cultured myotubes (41). Interestingly, ␤ 1a peptides from the same C-terminal region identified in our study were found to activate native and purified RyR1 channels fused into lipid bilayers (20,21). Moreover, microinjection of these peptides into flexor digitorum brevis fibers was reported to specifically enhance depolarization-induced Ca 2ϩ release (42), further supporting the idea that the C-terminal domain of ␤ 1a subunit directly interacts with RyR1 and that this interaction is involved in EC coupling signaling.…”
Section: Discussionmentioning
confidence: 57%
“…However, because no structural information was obtained in these studies, it is unclear whether the effects of ␤ 1a in EC coupling are simply due to an effect on DHPR positioning. Recent in vitro studies have shown that peptides fragments from the C-terminal domain of ␤ 1a modulate RyR1 channel function, giving support to the idea of a direct functional interaction between ␤ 1a and RyR1 (20). Mutational analysis of these peptides identified the critical motif responsible for RyR1 activation in a hydrophobic pocket formed by amino acid residues Leu 496 -Leu 500 -Trp 503 (21).…”
Section: Excitation-contraction (Ec)mentioning
confidence: 89%